EVALUASI TERHADAP PERUBAHAN STATUS BEBERAPA HARA TANAH SETELAH 10 TAHUN DI BUKIT GAJABUIH PADANG - Hermansah Hermansah; Juniarti Juniarti; Utami Maya Pribadi (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2008)
This experiment is about the evaluation of characteristic alteration of soil nutrients after ten years at tropical rain forest Bukit Gajabuih Gunung Gadut Padang. This experiment was conducted from November 2006 - April 2007. This experiment is arranged based on anova design with three treatments which was based on three great groups of land ( oxic-dystroudept (eutriccc, aquic), oxic-dystroudept (xanthic), oxic-typic-dystroudept (xanthic)). The purpose of this experiment was to study the alteration of soil fertility characteristics (K, Ca, Mg, Na, P and C/N) in ten years period (1995-2005) in tropical rain forest at Bukit Gajabuih Padang, to observe vegetation variety alteration, and the relationship with the land fertility characteristics. From the experiment was found that nutrient status of the soils altered after ten years (*1995-2005). Available P content increased about 77%, exchangeable Na and K increased 86,04% and 53.65%, respectively. On the other hand, exchangeable Mg and Ca decreased 3,05% and 65,88%, respectively. Land C/N ratio decreased about 21,39%. The experimental plot had low soil pH.Key Words: tropical rain forest, soil nutrient status